Analisis Sistem Pemanenan Air Hujan (PAH) untuk Memenuhi Kebutuhan Air Bersih pada Masjid Raya Sabilal Muhtadin di Banjarmasin - Anggita Aprillia Cahyani; Noordiah Helda (Jurnal Teknologi Berkelanjutan, 2022)
As the largest mosque in South Kalimantan Province, Sabilal Muhtadin Grand Mosque can accommodate several hundreds of people. Thus, it can lead to quite huge amount of water for ablution and other needs. On the other hand, in recent periods, high intensity rainfall occurred in some areas, including Banjarmasin City, causing excess surface runoff. To take advantage of this excess runoff, water conservation was carried out by using rain water harvesting techniques. This study was conducted to analyze the amount of clean water needs and analyze the potential use of rainwater harvesting system as an alternative source of clean water, in particular from mosque roof when it was raining. The results show that clean water need is 43,875 liters/day with an average number of jamaah of 375 people. In a year, the average need for clean water is 16,797.84 m³, while the average volume of rainwater that can be harvested is 13,827 m³. In summary, this rainwater harvesting potentially contributes to 85% of overall water use.